Enhancing audit understanding among waste bank managers to improve accountability - Nabillah Farras Luthfi; Bunga Anisah Harared; Yongki Rangga Yuda Nugraha (PT WIM Solusi Prima, 2026)
Bank Sampah Sri Rejeki still face challenges in achieving financial accountability due to limited understanding of audit concepts and the continued use of manual financial recording systems. This community service activity aims to enhance audit understanding among waste bank managers to improve financial accountability at Bank Sampah Sri Rejeki. The method used was participatory socialization through counseling, observation, discussion, and simple case studies conducted directly during waste weighing activities. The materials provided focused on the role of audit in waste banks, simple financial supervision, reconciliation of records, and transaction documentation. The results of the activity indicate that although the waste bank already has a clear division of tasks and orderly manual records, the absence of routine verification and reconciliation increases the risk of recording errors. After the activity, waste bank managers showed improved awareness of the importance of financial checking and verification as part of accountability to members. This activity demonstrates that strengthening basic audit understanding can be implemented effectively in community-based organizations to support transparency, accountability, and long-term sustainability.